Role of Antimicrobial Stewardship in Modulating Antibiotic Use and Mitigating Bacterial Resistance in a Tertiary Care Setting During COVID-19 - Zhang X; Zhou L; Peng P; Zhang W; Liang C (Infection and Drug Resistance)
Xueyan Zhang,1,* Lijuan Zhou,1,* Pingzhi Peng,2 Weiquan Zhang,2 Chunhong Liang2 1Department of Pharmacy, Sixth Affiliated Hospital of Guangxi Medical University, Yulin, Guangxi, 537000, People’s Republic of China; 2Office of Drug Clinical Trial Institution, Sixth Affiliated Hospital of Guangxi Medical University, Yulin, Guangxi, 537000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunhong Liang, Office of Drug Clinical Trial Institution, Sixth Affiliated Hospital of Guangxi Medical University, Yulin, Guangxi, 537000, People’s Republic of China, Tel +86-15778671091, Email lchhon@163.comPurpose: Despite the widespread adoption of antimicrobial stewardship (AMS) programs, their effectiveness varies because of differing regional policies and socioeconomic factors. This study aimed to assess the impact of AMS at a Chinese tertiary care hospital on inpatient antimicrobial use and bacterial resistance during the COVID-19 outbreak.Methods: An interrupted time-series regression analysis was conducted to compare inpatient antimicrobial use between pre- and post-intervention periods. The Chi-squared test and linear regression analysis were used to compare bacterial resistance and illustrate temporal trends in bacterial resistance, respectively.Results: Following the AMS strategy implementation, we observed a significant decrease in antimicrobial consumption at unrestricted (β 2 = − 6.38, P = 0.004), restricted (β 2 = − 17.81, P < 0.001), and special levels (β 2 = − 2.32, P < 0.001). Despite a reduction in the use of third-generation cephalosporins and macrolides (β 2 = − 6.85, P < 0.001; β 2 = − 2.82, P < 0.001), an increase in the trend of use was observed post-intervention (β 3 = 0.15, P < 0.001; β 3 = 0.04, P = 0.001). Methicillin resistance in Staphylococcus aureus significantly decreased (β = − 0.23, P < 0.001) from 52.85% to 40.92%. Conversely, the prevalence of carbapenem-resistant Klebsiella pneumonia increased from 4.69% to 10.87% (P < 0.001), whereas resistance to Acinetobacter baumannii and Pseudomonas aeruginosa marginally decreased (P< 0.05). We observed decreases in the antimicrobial utilization rate (β 2 = − 11.86, P = 0.003) and combination utilization rate (β 2 = − 12.36, P = 0.011) post-intervention. No significant changes in special-level antimicrobial and prophylactic agent use in category I incisional surgeries were observed.Conclusion: An AMS program in a Chinese tertiary facilitated effective management of antimicrobial use and reduction of bacterial resistance during the COVID-19 pandemic, in the context of combined infection prevention and control measures. The findings provide useful insights for the implementation of antimicrobial stewardship in future public health crises.Keywords: public health, antimicrobial management, healthcare strategy, COVID-19